Kokkuvõte kliinilisest auditist „Bariaatrilise ravi kvaliteet 2012. aastal opereeritud patsientidel“ - Kaur, Ilmar; Adamson, Rein; Miidla, Priit; Tikk, Toomas; Trudnikov, Andre (Eesti Arst, 2014)
Eesti Arst 2014; 93(10):559–560